Study of reading habits 1988 - Kalmar and Öland - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Kalmar and Öland. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. In this survey the respondent had to give an estimation on the share of households reading the local morning papers Barometern and Östra Småland respectively. Furthermore the respondent had to compare the two local papers with regard to a number of qualities. A battery of questions dealt with the local paper Östra Småland specifically. The respondents also had to indicate a number of reason why they listen to local radio, watch Swedish television, read morning papers and watch cabel-television.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of Kalmar and Öland. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. In this survey the respondent had to give an estimation on the share of households reading the local morning papers Barometern and Östra Småland respectively. Furthermore the respondent had to compare the two local papers with regard to a number of qualities. A battery of questions dealt with the local paper Östra Småland specifically. The respondents also had to indicate a number of reason why they listen to local radio, watch Swedish television, read morning papers and watch cabel-television.
Läsvanestudien 1988 - Kalmar och Öland
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap